Audit of the quality of intraoral periapical radiograph: An institutional study - Sunita Shankarrao Patankar; Freny R Karjodkar; Kaustubh P Sansare; Shalvi Vora (Wolters Kluwer Medknow Publications, 2019)
Objectives: To reduce the radiation exposure to patients, to improve the diagnostic proficiency of radiographs, and to collect data which will help decide the action of improvement in performance. Materials and Methods: The audit consisted of two cycles: Audit Cycle 1 analyzed randomly selected 400 recently taken intraoral periapical (IOPA) radiograph and the quality of each film was recorded according to subjective quality rating of radiograph given by the national board of radiation protection (NPRB) guidance and put them into Grades 1, 2, or 3. Audit Cycle 2 radiographs from Grades 2 and 3 were further randomly reevaluated to determine the causes of error and these are classified into faults due to positioning, exposure, and chemical processing. Frequency (n) and percentage (%) of outcome of various grades overall and with respect to independent variables will be compared using Chi-square test. Results: Of the 400 IOPA radiographs, 180 (45%) score Grade 1, 165 (41.3%) score Grade 2, and 55 (13.8%) score Grade 3. In Grade 2, IOPA radiographs of 163 (40.7%) were found to be positioning error, 45 (11.2%) exposure error, and 9 (5.5%) chemical processing. In Grade 3 (out of 57 IOPA), radiographs were rejected due to positioning faults in 45 (28.8%), exposure error in 7 (4.3%), and chemical processing in 3 (1.8%). Conclusion: The overall quality of radiographs was not found to be satisfactory when compared with standard recommendations of the National Board of Radiation Protection of UK. When the audit of the quality was done at regular intervals, it can be used as a guide to effective dose reduction and reduction of unnecessary irradiation of the patients and staff.